Kirkpatrick's four levels of training evaluation - Kirkpatrick, James D.; Kirkpatrick, Wendy Kayser (Association for Talent Development, 2016)
Presenting a powerful training evaluation methodology, this book provides innovative concepts, principles, techniques, and case studies that will help you to better train people, improve the way you work, and, ultimately, help your organization meet its most crucial goals. --